Dynamic biomarker and imaging changes from a phase II study of pre‐ and post‐surgical sunitinib. (2nd November 2021) - Welsh, Sarah J.; Thompson, Nicola; Warren, Anne; Priest, Andrew N.; Barrett, Tristan; Ursprung, Stephan; Gallagher, Ferdia A.; Zaccagna, Fulvio; Stewart, Grant D.; Fife, Kate M.; Matakidou, Athena; Machin, Andrea J.; et al.
Abstract : Objective: To explore translational biological and imaging biomarkers for sunitinib treatment before and after debulking nephrectomy in the NeoSun (European Union Drug Regulating Authorities Clinical Trials Database [EudraCT] number: 2005‐004502‐82) single‐centre, single‐arm, single‐agent, Phase II trial. Patients and Methods: Treatment‐naïve patients with metastatic renal cell carcinoma (mRCC) received 50 mg once daily sunitinib for 12 days pre‐surgically, then post‐surgery on 4 week‐on, 2 week‐off, repeating 6‐week cycles until disease progression in a single arm phase II trial. Structural and dynamic contrast‐enhanced magnet resonance imaging (DCE‐MRI) and research blood sampling were performed at baseline and after 12 days. Computed tomography imaging was performed at baseline and post‐surgery then every two cycles. The primary endpoint was objective response rate (Response Evaluation Criteria In Solid Tumors [RECIST]) excluding the resected kidney. Secondary endpoints included changes in DCE‐MRI of the tumour following pre‐surgery sunitinib, overall survival (OS), progression‐free survival (PFS), response duration, surgical morbidity/mortality, and toxicity. Translational and imaging endpoints were exploratory. Results: A total of 14 patients received pre‐surgery sunitinib, 71% (10/14) took the planned 12 doses. All underwent nephrectomy, and 13 recommenced sunitinib postoperatively. In all, 58.3% (seven of 12) of patients achieved partial or complete response (PR or CR) (95% confidence interval 27.7–84.8%). The median OS was 33.7 months and median PFS was 15.7 months. Amongst those achieving a PR or CR, the median response duration was 8.7 months. No unexpected surgical complications, sunitinib‐related toxicities, or surgical delays occurred. Within the translational endpoints, pre‐surgical sunitinib significantly increased necrosis, and reduced cluster of differentiation‐31 (CD31), Ki67, circulating vascular endothelial growth factor‐C (VEGF‐C), and transfer constant ( K Trans, measured using DCE‐MRI; all P  < 0.05). There was a trend for improved OS in patients with high baseline plasma VEGF‐C expression ( P  = 0.02). Reduction in radiological tumour volume after pre‐surgical sunitinib correlated with high percentage of solid tumour components at baseline (Spearman's coefficient ρ = 0.69, P  = 0.02). Conversely, the percentage tumour volume reduction correlated with lower baseline percentage necrosis (coefficient = −0.51, P  = 0.03). Conclusion: Neoadjuvant studies such as the NeoSun can safely and effectively explore translational biological and imaging endpoints.